Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/08916934.2015.1033687
|View full text |Cite
|
Sign up to set email alerts
|

The association between rs4684677 T/A polymorphism in preproghrelin gene and predisposition to autoimmune thyroid diseases in children

Abstract: Rs4684677 T/A polymorphisms in preproghrelin gene could contribute to development of AITDs in children and T allele is the main risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Most recently, based on the results of an analysis performed in a large cohort of GD patients, Yuan et al reported significant genetic heterogeneity between subjects with age of GD onset ≤20 and >20 years, suggesting it is reasonable to reduce the cut‐off value for the definition of early‐onset GD. However, data on the genetic risk factors in POGD are limited . In our multicentre study, we collected a large group of POGD patients and investigated similarities and differences in the genetic background between POGD and AOGD for the established and suggested GD/AITD risk loci .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, based on the results of an analysis performed in a large cohort of GD patients, Yuan et al reported significant genetic heterogeneity between subjects with age of GD onset ≤20 and >20 years, suggesting it is reasonable to reduce the cut‐off value for the definition of early‐onset GD. However, data on the genetic risk factors in POGD are limited . In our multicentre study, we collected a large group of POGD patients and investigated similarities and differences in the genetic background between POGD and AOGD for the established and suggested GD/AITD risk loci .…”
Section: Introductionmentioning
confidence: 99%
“…However, data on the genetic risk factors in POGD are limited. [18][19][20][21][22][23][24][25][26][27] In our multicentre study, we collected a large group of POGD patients and investigated similarities and differences in the genetic background between POGD and AOGD for the established and suggested GD/ AITD risk loci. Subsequently, we looked for genetic variants associated with age of GD onset in the entire cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was suggested that rs4684677 probably contributes to autoimmune thyroid disease predisposition in a case-control study that investigated polish children (p=0.002) [14], as well as increased women's waist circumference in a Spanish sample population [15]. No significant association was observed in a Brazilian population sample in a study conducted for gestational diabetes [16].…”
Section: The Polymorphism Rs4684677mentioning
confidence: 99%
“…First, the G protein-coupled receptor-39 (GPR39) was indicated as an obestatin cognate ligand receptor, but this is not supported by several authors, indicating the need for new and more accurate research [4][5][6]. However, that peptide clearly shows an important role in metabolism involved with anti-inflammatory and cardioprotective effects [7][8][9][10][11][12][13][14][15][16][17][18][19]. Furthermore, polymorphisms found in GHRL gene are also being associated with different clinical conditions [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Rs4684667 A/T also showed significant association with cognitive impairment in elder Spanish community dwelling individuals [20]. A variety of other studies provided supporting evidence for the role of rs4684677 T/A polymorphism in influencing metabolic syndrome, panic disorder, cancer, and autoimmune thyroid disease risks [2124]. …”
Section: Introductionmentioning
confidence: 99%